2.6q-3.9-5.7q=-4.1q-1.3

Simple and best practice solution for 2.6q-3.9-5.7q=-4.1q-1.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.6q-3.9-5.7q=-4.1q-1.3 equation:


Simplifying
2.6q + -3.9 + -5.7q = -4.1q + -1.3

Reorder the terms:
-3.9 + 2.6q + -5.7q = -4.1q + -1.3

Combine like terms: 2.6q + -5.7q = -3.1q
-3.9 + -3.1q = -4.1q + -1.3

Reorder the terms:
-3.9 + -3.1q = -1.3 + -4.1q

Solving
-3.9 + -3.1q = -1.3 + -4.1q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '4.1q' to each side of the equation.
-3.9 + -3.1q + 4.1q = -1.3 + -4.1q + 4.1q

Combine like terms: -3.1q + 4.1q = 1q
-3.9 + 1q = -1.3 + -4.1q + 4.1q

Combine like terms: -4.1q + 4.1q = 0.0
-3.9 + 1q = -1.3 + 0.0
-3.9 + 1q = -1.3

Add '3.9' to each side of the equation.
-3.9 + 3.9 + 1q = -1.3 + 3.9

Combine like terms: -3.9 + 3.9 = 0.0
0.0 + 1q = -1.3 + 3.9
1q = -1.3 + 3.9

Combine like terms: -1.3 + 3.9 = 2.6
1q = 2.6

Divide each side by '1'.
q = 2.6

Simplifying
q = 2.6

See similar equations:

| 3/2x=30 | | 36x61/45 | | 15x+2+x=18x+90-2x | | y-28=-41 | | -5y+5=-6y+2 | | 3/5s=12 | | 8(t-5)+7t=5(3t+5)-13 | | 1/2x1/9 | | 2+15x-21=14x-22 | | 1/2*1/9 | | -33p=-264 | | 2+15x-21=13x-22 | | Y-45=11 | | -2(2x-3)-(2x-6)+5=-5(x-1)-(2x+6)+3 | | y=-4x-31 | | a=5-9a+8 | | 6x+8y-2x-y= | | 3/4=87*9 | | 7x-12-2x=7x-9 | | (x-1)+(2x+3)+(2x+3)=180 | | 9=87/3/4 | | 15x-.75=13x-.50 | | 87=3/4/9 | | 15x/2+19=12x+7/2 | | 14/19/11 | | 9x^4-10x^2+1=0 | | 1(t-3)+7t=4(2t+4)-13 | | x=0.40(x+15) | | 76c=828 | | y-5=-1/8x | | 7x+3y=5 | | 196*47/49*1/16 |

Equations solver categories